Corporate governance, intellectual capital efficiency and performance of islamic banks : evidence from islamic countries - Aslam, Ejaz (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2020)
Islamic banking and finance industry has been growing exponentially, especially in recent decades. The rapid growth witnessed by this industry demands well-trained human resources at board or management level to play leadership roles under a good corporate governance structure. To address this issue, the current study has made a threefold contribution to the examination of Islamic banking performance. First, this study investigates the relationship between corporate governance and intellectual capital efficiency of Islamic banks. Second, it examines the impact of intellectual capital efficiency on Islamic banks' performance. Third, it determines the relationship between corporate governance and Islamic banks' performance using intellectual capital efficiency as a mediating variable. The sample size of this study consisted of I29 Islamic banks from 29 Islamic countries, from 2008 to 2017. The data sourced were analysed via 2SYS-GMM to assess the influence of corporate governance and intellectual capital efficiency on the Islamic banks' performance. The results show that board structures, particularly board size, non-executive directors, and audit committee, have positive and significant relationships with intellectual capital efficiency. These findings lending support to the resource dependence theory, where boards were enhancing the intellectual capital efficiency to detain a competitive advantage in the market. Similarly, the study finds that intellectual capital efficiency, mainly structural capital efficiency and relational capital efficiency, has a positive and significant relationship with Islamic banks' performance. Thus, the finding highlights the importance of intellectual capital efficiency for the rapid growth of Islamic banks. Moreover, the study provides evidence that corporate governance measure, particularly board size, has a negative and significant relationship with banks' performance; whereas, non-executive director, CEO duality, Shariah board, and audit committee have positive and significant relationships with banks' performance. Barron and Kenny's (1986) mediating test procedure reveals that intellectual capital efficiency mediates the relationship between corporate governance and Islamic banks' performance. Based on the findings of this study, it is envisaged that this study will benefit the research community, having incorporated different areas or research into one model. This study suggests that management and other regulatory bodies must recognise the effectiveness of corporate governance mechanism, along with the intellectual capital efficiency, in improving the performance of Islamic banks.